INNOVATIVE ICT ADOPTION, MARKET-SENSING CAPABILITY, KNOWLEDGE MANAGEMENT, AND INNOVATION OUTCOMES AMONG MALAYSIAN SMES - Mohd Yusof, Ahmad Nizam (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2026)
This study investigates the influence of innovative information and communication technologies (ICT) on the market-sensing and knowledge-management abilities of Malaysian small and medium-sized firms (SMEs). Data from a survey of 200 SMEs in the Klang Valley were examined through structural equation modelling. The results show that market sensing doesn't have a big effect on knowledge management or the growth of small or big innovations. Market logic can help us understand how organisations act, but it doesn't immediately affect the results of innovation in this case. Effective market sensing can help companies learn more about their consumers, competitors, and changes in the environment (Desarbo et al., 2021), but the study demonstrates that it is not a major factor that affects innovation.